A simple, fast and green nanofibers mat-based disk solid-phase extraction technique for chrysoidine analysis in soybean products. Issue 13 (17th March 2016) - Qi, Feifei; Li, Xiaoqing; Liu, Jingjing; Huang, Kaiping; Rong, Fei; Xu, Qian
Abstract : We proposed a simple and fast method for the determination of chrysoidine in soybean products. Abstract : A simple, fast and green sample preparation method followed by HPLC-DAD was developed for the determination of chrysoidine in soybean products. A polypyrrole (PPy) functionalized nanofibers mat (PPy-NFsM mat) was positioned in a home-made filter assembled to a nanofibers mat-based disk solid-phase extraction (NFsM-disk SPE) device for sample cleanup and preconcentration. After a simple extraction with alkaline ethanol–water solution, the sample extractants were diluted and directly purified by the technique. Then, the eluent was analyzed forthrightly by HPLC without an evaporation–concentration step. Compared to present methods, it was a faster sample preparation (10 min per sample) method with remarkably reduced organic solvent (15.7 mL). The developed method was validated by the analysis of six different kinds of spiked soybean products, resulting in satisfactory recoveries (78.2–106.5%; RSD ≤ 9.7%), and limit of quantitation (0.05 mg kg −1 ), which demonstrate the feasibility of the proposed method. In addition, the PPy NFsM mat could be reused three times excluding matrix interference.